A thousand words about running fitness tests - Kowalska, Małgorzata; Fehlau, Marcin; Cymerys, Maciej; Guzik, Przemysław (Journal of Medical Science, 2019)
Running is undertaken for different reasons, including improvement or maintenance of health and fitness. Many tests are employed for the estimation of the fitness in runners. In this review, we describe five field tests (Cooper test, Conconi test, 6-Minute Walk Test, 20-meter Multistage Fitness Test, and Harvard Step Test) and one laboratory cardiopulmonary exercise test (CPET) on a treadmill. A properly selected fitness test may help to estimate or measure the maximal oxygen consumption (VO2), thresholds for the aerobic and anaerobic metabolism, or restitution after the exercise. Such information is used for planning the training process, monitoring the progress of physical fitness or predicting the target distance or speed during competitions. In patients with cardiovascular or pulmonary diseases, this information may help to plan the intensity of daily activity or physical rehabilitation. Testing physical fitness is challenging, however when made appropriately, it delivers valuable physiological and clinical information.